How active and passive social media use affects impulse buying in Chinese college students? The roles of emotional responses, gender, materialism and self-control - Chen, Si; Zhi, Kuiyun; Chen, Yongjin (Frontiers in Psychology, 2022)
Social media plays a vital role in consumers’ purchasing decision making. There are still gaps in existing research on the relationship between divided dimensions of social media use and impulse buying, as well as the mediating and moderating effects therein. This study explored the mediation and moderation effects in the relationship between different social media usage patterns, emotional responses, and consumer impulse buying. Data from 479 college students who were social media users in China were analyzed using structural equation modeling. The results showed that active and passive social media use were significantly and positively associated with users’ enjoyment, whereas passive social media use significantly increased depression. Both enjoyment and depression were significantly and positively associated with users’ impulse buying. Materialism positively moderated the relationship between enjoyment and impulsive consumption, while self-control significantly reduced the effect of depression on impulse buying. These findings that emotion mediated and personality traits moderated relationships between social media use and impulse buying expand impulsive purchase literature and provide insights for guiding college students’ healthy use of social media and rational consumption.